Anthropo-geographical aspects of the Great Trek : 1836-1863 (Historia, 2021)
The  Great Trek denotes more than the  literal  departure from  the CapeColony.   It  also denotes the  settlement in  the  interior,  the  organization ofa state and  community, the  resultant political  movements and the structureor  pattern of the  new state.  The  Great Trek  extended over a long  period,and  must be viewed in  that  light.    It  must be  considered up  to  the  stagewhen it  came to  a more or  less definite end and a  new and  different phaseset in.  To my mind the years from  1836 to  1863 constitute the Trek period-the  life   span of  about one generation.   In  that  period  the  Trek  enteredmaturity.It  is  the  Trek  period  taken as a  whole  that we now wish to  illustratefrom  a  geographical point  of  view.   One should bear in  mind  that man isclosely bound  up  with  his  environment and  that  the  political  iflstitutionsand the movements or  activities of  human groups are influenced in  various\\'ays by  their  physical environment.   When considering the  political  life,we  might  first  of  all  determine the  part  played  by  g~ographical featuresin  the causes of the Trek,  then investigate the  movement itself,  and finallyconsider the  settlement and the  forces arising  therefrom
Keywords: Frontier difficulties; Anthropology; Geography; Great Trek; Political groups; Civil war